the effect of story telling method on students’ speaking ability at the seventh grade of SMP Negeri 2 Satap Lumut in 2018/2019 academic year - Kasmas Julisman (JURNAL LINER (Language Intelligence and Educational Research), 2020)
The purposes of this research are to know: 1) the application of Story Telling Method in teaching speaking at the Seventh Grade Students of SMP Negeri 2 Satap Lumut. 2) the students’ speaking ability before and after using Story Telling Method at the Seventh Grade of SMP Negeri 2 Satap Lumut. 3) whether there is a significant effect of students’ speaking ability after using Story Telling Method at the Seventh Grade of SMP Negeri 2 Satap Lumut. Method of the research was experimental. The population of this research was the Seventh Grade of SMP Negeri 2 Satap Lumut. It consists of 42 students. Total sampling was the sampling technique in this research to get sample. It consists of 42 students. The technique of collecting data were observation sheet and test. The result mean score of the application story telling method was 3.8, it was categorized “Very Good”. The result showed score before using story telling method was 40.8, it was categorized “Fail”. While the mean score of the students’ speaking ability after using story telling method was 60.4, it was categorized “Enough”. The result of ttest was 15.95 and ttable was 2.02. It means that there is a significant effect of using story telling method on students’ speaking ability at the Seventh Grade of SMP Negeri 2 Satap Lumut.